ISOLASI DAN KARAKTERISASI BAKTERI PENGHASIL SENYAWA ANTIBAKTERI YANG BERASOSIASI DENGAN KARANG BATU DARI PERAIRAN BITUNG DAN SPONS DARI SELAT MAKASSAR - SUNNY, FRANSISCA; KURNIATI, TRI HANDAYANI; HATMANTI, ARIANI (LPPM Universitas Negeri Jakarta, 2015)
ABSTRACT Recently the needs of antibacterial compounds is increasing. This is due to the bacterial resistence to common antibacterial compounds. coral and sponge-ssociated bacteria are potential producer of antibacterial compounds. This research was aim to obtain coral and sponge-associated bacteria that could produce antibacterial compound. coral associated-bacteria was isolated from Bitung and was isolated in Marine Agar by pour plate method. The antibacterial compounds were obtained by extraction using ethyl acetate and acetone. The antibacterial assay was performed by agar diffusion method using paper discs and was performed by testing with Staphylococcus aureus, Bacillus subtilis, Vibrio cholerae biotipe El Tor, and Escherichia coli. Total 37 isolate was isolated from corals and 25 isolate from sponge obtained from Selat Makassar. Based on the assay, only bacteria from sponge that showed antibacterial activity. Two sponge-associated bacteria, S.5-8 and S.2-1 NRBC were found to inhibit S. aureus. From those isolates, isolate S.5-8 produced bigger clear zone (2,6 mm) than S.2-1 NRBC (1,5mm). S.5-8 could hydrolize gelatine whereas S.2-1 NRBC showed positive result on oxidase test and was able to fement xilose and arabinose to produce acid. Key words: antibacterial activity, association, characterization, coral, isolation, sponge